The Role of Estrogen and Thyroid Hormones in Zebrafish Visual System Function - Cohen, Annastelle; Popowitz, Jeremy; Delbridge-Perry, Mikayla; Rowe, Cassie J.; Connaughton, Victoria P. (Frontiers in Pharmacology, 2022)
Visual system development is a highly complex process involving coordination of environmental cues, cell pathways, and integration of functional circuits. Consequently, a change to any step, due to a mutation or chemical exposure, can lead to deleterious consequences. One class of chemicals known to have both overt and subtle effects on the visual system is endocrine disrupting compounds (EDCs). EDCs are environmental contaminants which alter hormonal signaling by either preventing compound synthesis or binding to postsynaptic receptors. Interestingly, recent work has identified neuronal and sensory systems, particularly vision, as targets for EDCs. In particular, estrogenic and thyroidogenic signaling have been identified as critical modulators of proper visual system development and function. Here, we summarize and review this work, from our lab and others, focusing on behavioral, physiological, and molecular data collected in zebrafish. We also discuss different exposure regimes used, including long-lasting effects of developmental exposure. Overall, zebrafish are a model of choice to examine the impact of EDCs and other compounds targeting estrogen and thyroid signaling and the consequences of exposure in visual system development and function.